Лексична картотека і корпус як інструмент лексикографічного моделювання слова - Карпіловська, Є. (Лексикографічний бюлетень, 2015)
The conception of modern multiparametrical lexical card index – the so-called card index “portraits of words” – unlike of traditional card index of quotations is concidered. Such card index of new type should include information about the system and text properties of words that would fully refl ect their semantics, syntagmatics, paradigmatics, epidygmatics, chronology, pragmatics. It should interact with the language corpus and broad base of texts for the modelling of real state of modern lexicon.